Revisiting the impact of energy consumption, foreign direct investment, and geopolitical risk on CO2 emissions: Comparing developed and developing countries - Ma, Wei; Nasriddinov, Fazliddin; Haseeb, Mohammad; Ray, Samrat; Kamal, Mustafa; Khalid, Noreen; Ur Rehman, Masood (Frontiers in Environmental Science, 2022)
A growing body of literature probes the impact of geopolitical risk (GPR) on CO2 emissions. However, no study compares the findings in the case of developed and developing countries. Hence, this study aims to probe the impact of GPR on CO2 emissions for selected developed and developing countries while controlling for energy consumption, foreign direct investment, and economic growth. For this purpose, we make use of a panel dataset covering the period 1990-2020. In the long-run, we report that the Environmental Kuznets Curve hypothesis exists for developing countries. Next, the pollution haven hypothesis is validated for the developed countries in the long-run. Also, GPR escalates emissions for developed and developing countries in the long-run. In the short-run, the Environmental Kuznets Curve and pollution haven hypothesis are found invalid. Moreover, in the short-run, GPR impedes emissions in both developed and developing countries. Further, energy consumption upsurges emissions across all samples (i.e., either developed or developing countries) in either its short- or long-run. The heterogeneous findings across the long- and short-run, for developed and developing countries, propose to formulate unalike policies for countries with different levels of income.